Murine models of renal ischemia reperfusion injury: An opportunity for refinement using noninvasive monitoring methods. Issue 5 (9th March 2022) - Harwood, Rachel; Bridge, Joshua; Ressel, Lorenzo; Scarfe, Lauren; Sharkey, Jack; Czanner, Gabriela; Kalra, Philip A; Odudu, Aghogho; Kenny, Simon; Wilm, Bettina; Murray, Patricia
Abstract: Background: Renal ischemia reperfusion injury (R‐IRI) can cause acute kidney injury (AKI) and chronic kidney disease (CKD), resulting in significant morbidity and mortality. To understand the underlying mechanisms, reproducible small‐animal models of AKI and CKD are needed. We describe how innovative technologies for measuring kidney function noninvasively in small rodents allow successful refinement of the R‐IRI models, and offer the unique opportunity to monitor longitudinally in individual animals the transition from AKI to CKD. Methods: Male BALB/c mice underwent bilateral renal pedicle clamping (AKI) or unilateral renal pedicle clamping with delayed contralateral nephrectomy (CKD) under isoflurane anesthetic. Transdermal GFR monitoring and multispectral optoacoustic tomography (MSOT) in combination with statistical analysis were used to identify and standardize variables within these models. Results: Pre‐clamping anesthetic time was one of the most important predictors of AKI severity after R‐IRI. Standardizing pre‐clamping time resulted in a more predictably severe AKI model. In the CKD model, MSOT demonstrated initial improvement in renal function, followed by significant progressive reduction in function between weeks 2 and 4. Performing contralateral nephrectomy on day 14 enabled the development of CKD with minimal mortality. Conclusions: Noninvasive monitoring of global and individual renal function after R‐IRI is feasible and reproducible. These techniques can facilitate refinement of kidney injury models and enable the degree of injury seen in preclinical models to be translated to those seen in the clinical setting. Thus, future therapies can be tested in a clinically relevant, noninvasive manner. Abstract : Noninvasive methods of measuring murine glomerular filtration rate (GFR) are used to refine both acute and chronic models of renal ischemia reperfusion injury (r‐IRI). Transdermal GFR monitoring revealed that standardization of the anesthetic duration prior to clamping reduces the variability of the acute injury model. Multispectral optoacoustic tomography (MSOT) enabled refinement of the chronic kidney disease model resulting in sustained reduction of the global GFR after r‐IRI in a humane way.